Solar Energy Potential and Its Utilization in Perovskite-Based Solar Cells for Selected Sites in Nepal - Adhikari, Krishna Raj (Tribhuvan University Journal, 2019)
The measurements of solar radiation for Biratnagar (BRT), Kathmandu (KTM), Pokhara (PKR) and Jumla (JML) have been undertaken using CMP 6 pyranometers from SAHR/IOE/TU, Nepal. Solar radiation and the other meteorological data have been collected from the archives of Department of Hydrology and Meteorology, Government of Nepal (DHM/GoN) to analyze the daily Global Solar Radiation (GSR). In this study, perovskite-based solar cells with the configuration Au/SpiroOMETAD/MAPbI3/TiO2/FTO have been simulated using Solar Cell Capacitance Simulator (SCAPS). The power conversion efficiency (PCE) of the cell is found to be 22.67, 22.69, 22.77 and 22.80% in BRT, KTM, PKR and JML respectively, almost similar and better performance, whereas the solar cell performs better in JML due to the high solar irradiance.